Transcriptomic and Mutational Analysis Discovering Distinct Molecular Characteristics Among Chinese Thymic Epithelial Tumor Patients - Liang, Naixin; Liu, Lei; Huang, Cheng; Liu, Hongsheng; Guo, Chao; Li, Ji; Wang, Weiwei; Li, Nan; Lin, Rui; Wang, Tao; Ding, Lieming; Mao, Li; et al. (Frontiers in Oncology, 2021)
Introduction: Thymic epithelial tumors (TETs) are malignancies arising from the epithelium of the thymic gland, rare but with relatively favorable prognosis. TETs have different pathological subtypes: thymomas and thymic carcinoma, and they show different clinical characteristics regarding prognosis, pathology, and molecular profiles, etc. Although some studies have investigated the pathogenesis of TETs, more molecular data is still needed to further understand the underlying mechanisms among different TETs subtypes and populations. Methods: In this study, we performed targeted gene panel sequencing and whole transcriptome sequencing on the tumor tissues from 27 Chinese TET patients, including 24 thymomas (A, AB, and B subtypes) and 3 thymic squamous cell carcinomas. We analyzed the genetic variations and differentially expressed genes among multiple TET subtypes. Moreover, we compared our data with the published The Cancer Genome Atlas (TCGA) TET data on both the genetic and transcriptomic levels. Results: Compared with the TCGA TET genomic data, we found that NF1 and ATM were the most frequently mutated genes (each with a frequency of 11%, 3/27). The GTF2I mutation was mainly enriched in subtype A and AB thymomas, consistent with the previous reports. RNA-seq results unveiled that the genes related to thymus development (FGF7, FGF10 and CLDN4) were highly expressed in certain TET subtypes, implicating that the developmental process of thymus might be linked to the tumorigenesis of these subtypes. We found high expression of CD274 (PD-L1) in B2 and B3 thymoma samples, and validated its expression using immunohistochemistry (IHC). Based on the expression profiles, we further established a machine learning model to predict the myasthenia gravis status of TET patients and achieved 90% sensitivity and 70.6% specificity in the testing cohort. Conclusion: This study provides the first genomic and transcriptomic analysis of a Chinese TET cohort. The high expression of genes involved in thymus developmental processes suggests the potential association between tumorigenesis of TETs and dysregulation of developmental pathways. The high expression of PD-L1 in B2 and B3 thymomas support the potential application of immunotherapy on certain thymoma subtypes.